Intelligent glove for sign language communication - Navaitthiporn, Nitipon; Rithcharung, Preeyarat; Hattapath, Phitnaree; Pintavirooj, C. (My University, 2019)
Communication is very important in daily life while many people in Thailand cannot communicate by talking. On the other hand, they can communicate only sign language. The sign language used in a specific group of people, but other people cannot understand. Therefore, we decided to do a project about glove for sign language communication. This research created a hand glove for deaf and mute people to provide better communication between disabling and normal people. We applied computer programming by used the flex sensor and GY-521 Module. The flex sensor has measured the bent of fingers and generated an analog output. GY-521 Module is use for measured the direction and movement of the hand. After got data from both sensors, it will send to Arduino IDE converted all the data to alphabet and text before converted to speech. Then we tested the accuracy of the glove, it has accuracy about 70-100% which depends on another factor. From this process, we got a hand glove for sign language communication. This glove will help deaf and mute people to communicate more efficiently.
Keywords: communication; deaf; mute; sign language